Day 3 Wed, October 28, 2020 2020
DOI: 10.2118/201258-ms
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Wettability on Vaporization of Hydrocarbon Solvents in Nano Capillaries

Abstract: Tight rock reservoirs have gained popularity and become a subject of great interest due to their huge recovery potential. A substantial portion of the potential hydrocarbon could be removed from the reservoir by injecting solvent gases (hydrocarbon or CO2) as an Enhanced Oil Recovery (EOR) application. Achieving a precise modeling of these processes and accurate description of hydrocarbon dynamics requires a clear understanding of phase-change behaviour in confined (capillary) medium. It was previously shown t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…As a result, shifted vaporization pressures of propane, heptane, and octane were noticed in the permeable rocks, including the tight rocks (shale and tight sandstone) at which a high percentage of their pore diameters are in nanoscale (< 100 nm). This paper is a continuation of our previous works [5][6][7]18,20 , and it investigates the vaporization temperature of pure-component hydrocarbon solvents, binary mixtures, and ternary mixtures in different reservoir rocks and under various pressures. Experimental data and evidences are provided as to the effect of confined environment (nano-pores and high capillary pressures) on the phase behavior (vaporization) of solvents.…”
Section: List Of Symbols Pr-eosmentioning
confidence: 94%
See 4 more Smart Citations
“…As a result, shifted vaporization pressures of propane, heptane, and octane were noticed in the permeable rocks, including the tight rocks (shale and tight sandstone) at which a high percentage of their pore diameters are in nanoscale (< 100 nm). This paper is a continuation of our previous works [5][6][7]18,20 , and it investigates the vaporization temperature of pure-component hydrocarbon solvents, binary mixtures, and ternary mixtures in different reservoir rocks and under various pressures. Experimental data and evidences are provided as to the effect of confined environment (nano-pores and high capillary pressures) on the phase behavior (vaporization) of solvents.…”
Section: List Of Symbols Pr-eosmentioning
confidence: 94%
“…The correct estimation of temperature is beneficial in reducing the operational cost by eliminating the need for excessive heat energy. Pore size distribution analysis (PSDA) was conducted previously in our prior works [6][7][8][9][10][11][12][13][14][15][16][17][18] to experimentally measure the distribution of pore sizes in several reservoir rocks. These studies showed that nearly 4.5% of the pore volume in permeable rocks (Berea sandstone and Indiana limestone) are of nano-size, despite their relatively high permeabilities.…”
Section: Problem Statement and Solution Methodologymentioning
confidence: 99%
See 3 more Smart Citations